Pengembangan Media Pembelajaran Matematika RIMath Materi Himpunan Terintegrasi Al-Quran Untuk Memfasilitasi Literasi Matematis Siswa - Achmad Miftachul Ulum; Mochammad Ainul Qodri Asyari; Ulfa Masamah (Jurnal Karya Pendidikan Matematika, 2024)
Digital literacy is a skill that learners must have. This ability is the basis in shaping students' critical and creative reasoning. In shaping students' mathematical literacy, interesting learning media is needed. This learning media can be in the form of ICT or Manipulative. The RIMath application is an android-based learning media that can facilitate students' mathematical literacy. RIMath learning media presents mathematics learning that applies contextual problems while integrating the Qur'an. The type of research used in this study is R&D (Research and Development) using the 4D method (Define, Design, Develop and Disseminate). RIMath learning media will be validated to experts to ensure the quality of this learning media. RIMath learning media will also be tested with students to ensure that the RIMath application can facilitate students' mathematical literacy. RIMath learning media gets a feasibility percentage of 78.283%. This percentage proves that RIMath learning media is included in the "feasible" category to be used by students in learning mathematics. In a t-test experiment, RIMath learning is proven to improve students' mathematical literacy by working on math problems.